Strategi Guru Pada Pembentukan Penanaman Nilai-Nilai Pendidikan Karakter Disiplin Anak Pada Siswa Kelas 5 di SDN 106 kota Bengkulu - Intan Wulan Sari; Depi Fitriani; Yimita Sari; Erike Agustin Rusmana (Yayasan Darusssalam Bengkulu, 2024)
This research is field research with the aim of finding out the strategies and problems of the homeroom teacher, for example, students still often violate school rules. faced by teachers in cultivating the disciplinary character of grade 5 students at SDN 106 Bengkulu city. The research uses research methods with a qualitative descriptive approach with research subjects namely homeroom teachers and grade 5 students. Data collection techniques use observation and interview techniques. This interview technique was carried out to obtain information regarding the strategies and problems faced by teachers in cultivating students' disciplined character. The data analysis used by researchers went through three stages such as data reduction, data display and drawing conclusions. Based on the results of the data analysis that has been carried out, the teacher has done as much as possible to improve the disciplined character of students in motivating and making learning plans that can improve the discipline of students' character. However, in developing students' disciplined character, there are several problems faced.